Perancangan SITANI Sebagai Media Informasi Bagi Petani - Eko Harry Pratisto; Arif Budi Waluyo (IJAI (Indonesian Journal of Applied Informatics), 2017)
Agriculture is one source of livelihood of people in Surakarta. However, there are  some problems that occur in agriculture, such as: the shortage of agricultural goods, the difficulty of obtaining workshop activities information, and difficulty to sell crops at harvest periode  for the arragement  price from middlemen.SITANI application is develop using waterfall method and built using  Java programming language with tool Android Studio. The design includes table of functional requirements, use case diagram, ERD, activity diagrams, and interface design. Application testing is done using quistionnaire.The results of this research is the creation of android-based application with modules SITANI advertsement, workshop activities information, and ordering goods.